PENGARUH MOTIVASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR DINAS PENDIDIKAN DAN OLAH RAGA PROVINSI KALIMANTAN TIMUR - Safril Setiawan (ADMINISTRASI PUBLIK, 2020)
Syafril Setiawan, Study Program of Public Administration, Department of State Administration, Faculty of Social and Political Sciences, with the title "The Effect of Work Motivation on Employee Work Productivity at the Office of Education and Sports in East Kalimantan Province". under the guidance of Ms. Salasiah, S. Sos., M.Sc and Mr. Drs. H. Maskan, AF., M.Sc.This research is motivated by the leadership function of motivating the work of East Kalimantan Dispora employees to improve employee work productivity.The purpose of this study was to find out how the work motivation of employees at the East Kalimantan Dispora Office. The type of research or explanation used is descriptive quantitative used to analyze the relationship between research variables. The type of data used is questionnaire, observation, interview, and documentationFrom the results of the study found that work motivation on employee work productivity has a very positive effect, this can be proven by the calculation of R2 determination obtained values of 0.656 or 65.6% and 34.4% are influenced by other factors. From the t test hypothesis test results obtained t count greater than t table, where 3,612 > 1,677.Syafril Setiawan, Study Program of Public Administration, Department of State Administration, Faculty of Social and Political Sciences, with the title "The Effect of Work Motivation on Employee Work Productivity at the Office of Education and Sports in East Kalimantan Province". under the guidance of Ms. Salasiah, S. Sos., M.Sc and Mr. Drs. H. Maskan, AF., M.Sc.This research is motivated by the leadership function of motivating the work of East Kalimantan Dispora employees to improve employee work productivity.The purpose of this study was to find out how the work motivation of employees at the East Kalimantan Dispora Office. The type of research or explanation used is descriptive quantitative used to analyze the relationship between research variables. The type of data used is questionnaire, observation, interview, and documentationFrom the results of the study found that work motivation on employee work productivity has a very positive effect, this can be proven by the calculation of R2 determination obtained values of 0.656 or 65.6% and 34.4% are influenced by other factors. From the t test hypothesis test results obtained t count greater than t table, where 3,612 > 1,677.  Keywords: Dispora Motivation, Productivity, East Kalimantan